Secretaries of the Interior: Narratorial Collaboration in Sarah Scott's Millenium Hall. - Wandless, William H. (Eighteenth Century Fiction)
A literary criticism of the book "A Description of Millenium Hall" by Sarah Scott is presented. The book explores the relationship between the narrator of the book and the novel's character Mrs. Maynard. The didactic nature of the novel is explored and the audience is considered. An overview of the story is also given.